Ethnoveterinary Therapeutic Practices and Conservation Status of the Medicinal Flora of Chamla Valley, Khyber Pakhtunkhwa, Pakistan - Khan, Khalid; Rahman, Inayat Ur; Calixto, Eduardo Soares; Ali, Niaz; Ijaz, Farhana (Frontiers in Veterinary Science, 2019)
Domestic animals play a very important role in the human civilization. Besides human being, plants are used as medicines for many domestic animals. The therapeutic practices are very common among the tribes of Chamla, rich in ethnoveterinary medicinal plants. Due to poor availability of modern healthcare facilities and poverty of indigenous people, they depend on local medicinal plants for the healthcare of their domestic animals. This study is the first attempt to document the indigenous knowledge and evaluate the conservation status of medicinal plants and practices of herbal remedies by the local people of Chamla Valley in the treatment of their livestock. Semi-structured questionnaire was used and 120 local inhabitants were interviewed to note the traditional practices regarding plant species uses. Well-known statistical indices, Use Value formula and Relative Frequency Citations were used for quantification of the recorded data. It was observed that 50 medicinal plants belonging to 38 families were reported, where Poaceae was the most cited. The common livestock are goats, sheep, buffalos, cows, bulls and donkeys. Most of the herbs, which are used in livestock treatment, are wild and few plants are cultivated. The common livestock diseases are red water, three days sickness, diarrhea, tympany and indigestion among others. Most of the plants are used in fresh condition. According to the results, Brassica nigra was used for placenta retention, Butea monosperma for constipation, Calotropis procera for indigestion and three days sickness. Canabis sativa, Cedrella serrata, Allium sativum and Origanum vulgare were used for fever. The traditional plant collection techniques have resulted in huge losses of these valuable plant resources. The ethnobotanical conservation assessment revealed that due to increased exploitation and un-sustainable harvesting, 49% of these economically valued medicinal plant species are decreasing in last 30 years. Some of the plants are only present on high altitudes while they had been finished in the foothills like Paeonia emodi and Berberis lycium. Lack of scientific knowledge, ignorance, poverty and joblessness, as well as land development, construction and fires, add more pressure on flora and fauna of the area and various species are under the threat of extinction.